Financial Inclusion as a Bridge Between Capital Markets and Growth: Inklusi Keuangan sebagai Jembatan Antara Pasar Modal dan Pertumbuhan - Ratte, Rosalena Belo; Middin, Muslianti; Rasyid, Syarifuddin; Darmawati, Darmawati (Academia Open, 2025)
General Background: Capital markets are widely recognized as critical drivers of economic growth through efficient resource allocation and investment mobilization. Specific Background: In Indonesia, the extent to which capital markets contribute to growth may be contingent on the inclusiveness of the financial system. Knowledge Gap: However, limited research systematically explores the mediating role of financial inclusion in this relationship within the Indonesian context. Aims: This study conducts a Systematic Literature Review (SLR) to evaluate existing literature on the interconnection between capital markets, financial inclusion, and economic growth, with particular attention to financial inclusion as a mediating factor. Results: The synthesis reveals that capital markets can significantly influence economic growth, but their effectiveness is moderated by the depth and accessibility of financial inclusion. Novelty: This review highlights the dual importance of market development and inclusive access to financial services, offering a nuanced understanding of how capital markets can equitably support national growth. Implications: Findings underscore the need for policy frameworks that not only deepen capital markets but also enhance inclusive financial infrastructure to maximize economic benefits across society. Highlights: Highlights the mediating role of financial inclusion in economic growth. Synthesizes Indonesian studies using a Systematic Literature Review method. Emphasizes policy implications for inclusive financial development. Keywords: Capital Market, Economic Growth, Financial Inclusion